How Do Ideas Become General in their Signification? - Alexandros Tillas (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
Abstraction is one of the central notions in philosophy and cognitive science. Though its origins are often traced to Locke, various senses of abstraction have been developed in fields as diverse as philosophy, psychology, cognitive science, artificial intelligence, and computer science (e.g. Barsalou 2005). The notion of abstraction on which I am focusing here is as that of a process of similarities recognition across instances of a given kind involving progressive exclusion of instance details. As such, abstraction plays a major role in concept-formation and learning. Traditionally, abstraction models have been deemed circular (e.g. Berkeley 1710/1957), while in recent years abstraction models have also come under fire for being incoherent (e.g. Hendriks-Jansen 1996), requiring large conceptual resources in order to operate, and so forth. Here, I flesh out a psychological process on the basis of which general ideas are formed out of representations of particulars. The main characteristics of the suggested view are that abstract representations are structured entities with general representational powers, while a major role is given to top-down effects in perception. I argue that the challenges that both traditional and modern abstraction accounts faced are avoided in the light of the present suggestion.
Keywords: abstraction; general ideas; concept individuation; top-down effects in perception; Hebbian learning; classical conditioning